Dynamic features of the learning activity of the future teacher as a teacher interaction subject - Коць, Михайло Онисимович; Kots, Mykhailo O. (Ариэльский университетский центр в Самарии (г. Ариэль, Израиль), 2014)
This article deals with theoretical analysis and empirical investigation of educational activity dynamics of future teachers. Activity, awareness, mutual commitment are peculiar to educational interactions by both sides – the students (student) – a teacher – who act as subjects where coordinated action is the result and amplifies by mental state of contact are grounded. Methodological meaning of the notion activity in relation to psychological research, primarily in principle activity of the subject is highlighted Thus activity serves special quality of interaction between subject and objective reality, in such way of self-expression and self-realization of the individual for which either achieved or there is no quality as a complete, independent and self-intelligent subject. Author understanding of the formation of future teachers as the subject interaction involves the interaction of a dynamic system, and its structural basis is formed in the context of educational activities and its contents – is followed by the formation of certain properties. 779 college students from the first to the fifth year of study take part in the investigation. A set of such learning activities characteristics as potential activity, its regulation, the dynamics of implementation activity and self-esteem of learning activity results are the display of students’ learning activities have studied. The differences in students learning activity, namely the first-year and fifth-year students are disposed to training motivation, the second-year students – performing dynamic of implementation activity, the third and the fourth year – ability to learn have been distinguished In general, students focused on learning, are motivated to learn and are active in it. The variable rates of students learning activity are interdependent and vary according to the year of study, and the activity is an important factor of the educational interaction as a process and the formation of future teachers as a result have been proved.
Keywords: future teacher; subject; learning activity; educational process